SUBORDINATION RESULTS FOR A CERTAIN SUBCLASS OF NON-BAZILEVIC ANALYTIC FUNCTIONS DEFINED BY LINEAR OPERATOR - Alamoush, Adnan G.; Darus, Maslina (Italian Journal of Pure and Applied Mathematics, 2015)
In this work, by making use of the principle of subordination, we introduce a certain subclass of non-Bazilevic analytic functions defined by linear operator. Such results as subordination and superordination, sandwich theorem and inequality properties are given.